Effect of two-phase tapering method on certain physiological variables, fatigue resistance, stroke rate and record level of 200m reestyle for youth swimmers - Hossam-Eldeen, F. (Science, Movement & Health, 2019)
Purpose. Duringthe stage Tapering in order to determine the best of these methods and suitability for specialized distances for swimmers, and to guide researchers to study the different variables of methods of decline in size and determine the training, physiological, physical, and psychological effects of the use of methods for selected samples Roll of swimmers. This research aims to identify the effect of two-phase of Tapering method on some physiological variables Creatine Phosphokinase (CPK), lactic acid rate, heart rate), fatigue resistance, and stroke rate. in addition, explore the relationship between physiological variables, fatigue resistance, stroke rate, and the record level of 200m freestyle. Methods. The sample was chosen from the swimmers of 6 October City Sports Club for the stage of 17 years of males, (10) male swimmers. Results. Statistical analyses showed a positive correlation with statistically significant relationship between fatigue resistance and the record level of (200m freestyle), while there were no correlations with statistical significance between the other variables and the record level. Conclusions. Under the conditions of our study, the two-phase decrease in volume (Tapering) affected in all variables, while it did not affect swimmers' ability to resist fatigue during a 200-meter race distance, possibly due to the nature of the 200-meter high-speed race.